A simple scheme for bibliography acquisition using DOI content negotiation proxy. Issue 6 (28th October 2014) - Ma, Kun; Yang, Bo
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to study a bibliography acquisition approach to verify the bibliography by author name from the integrated system and the metadata from the digital object identifier (DOI) content negotiation proxy. As managed scientific research papers increase at a higher rate, an accurate and automated scheme for bibliography acquisition is desirable. Design/methodology/approach – This study develops a framework using DOI content negotiation proxy as context for the entering of the bibliography. The bibliography acquisition architecture is composed of three point of views to reduce the complexity: terminal UI, service deployed in the cloud and DOI content negotiation proxy. To simplify the service interface and support many kinds of bibliographic formats, this paper presents the independent BibModel and its template-based model transformation engine to support rich bibliographic records. Findings – An important finding of this article is that we do some significant development work to combine the open CrossCite DOI content service and DOI resolvers of registry agencies. As more than 95 per cent of DOIs are owned or managed by CrossRef, DataCite, ISTIC and mEDTA DOI registry agencies, it is a common universal approach for the scientific research paper results with DOIs. Practical implications – Through a simple method built quickly from freely available parts, it is partially successful, suggesting the scheme can be integrated with third-party systems, such as the management system of scientific research results and the electronic journal management system. The analysis of the application's effect shows the ability to verify the authenticity of the paper by author name from the system and the metadata from our DOI content negotiation proxy. Originality/value – This paper proposes an original and simple framework to acquire the metadata of bibliographies automatically. No detailed evaluative study has been carried out supporting both DOI content negotiation and resolver. This work shows how to implement the acquisition approach and how to integrate this framework with the current system.